An investigation of gender differences in a representative sample of juveniles detained in Connecticut. (January 2015) - Grigorenko, Elena L.; Sullivan, Tami; Chapman, John
Abstract: As the number of females served by the juvenile justice system in the United States continues to grow, both in absolute terms and relative to the number of males, it is important to understand both the general and specific characteristics of delinquent girls and boys regarding their patterns of offending and risk variables. Using systematic random sampling, 20% of all admittees to the state-run juvenile detention centers in the state of Connecticut, USA, were included in a chart review study, forming a sample (n = 371, 30.2% girls, age range 11–19 years; mean age = 14.45, sd = 1.05) that was analyzed for gender differences with regard to characteristics of offenses. These characteristics were examined for their potential associations with indicators of risk that are routinely collected at admission to detention. Findings indicate a complex set of associations between indicators of offense and risk, highlighting the importance not only of gender, but also of racial/ethnic differences, whose modulating effects appear to be important in understanding these associations. Specifically, girls in detention are characterized by a number of dimensions, some of which align with those for boys and some that are more gender-specific. For example, girls, as a group, demonstrated higher levels of substance abuse, suicide ideation, victimization, and mental-health variability, but these higher scores are more characteristic of girls from minority backgrounds. More research is needed to understand the profiles of juveniles in detention as the variables considered in this work that map onto the literature at large have resulted in effects of small magnitude.